The Effect of Number Line Teaching Aids on Mathematics Learning Outcomes Material on Operations to Count Integers Addition and Subtraction of Class V Students at SD Negeri 191769 Tembung - Debora Florentina; Laurensia Masri Perangin Angin; Marintan Evelyn Marbun; Rani Shintiya; Wanda Hamidah Harahap (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to investigate the effect of the use of number line teaching aids on mathematics learning outcomes, especially in the material of addition and subtraction integer arithmetic operations, in class V SD Negeri 191769 Tembung. Number line teaching aids are used as learning media that can help students understand the concept of integer arithmetic operations better. This study uses the Pre-experimental method. The research method is used to examine a causal relationship between two or more variables without using randomization or a control group. The research participants were fifth grade students at SD Negeri 191769 Tembung. Data on mathematics learning outcomes were collected through tests that included addition and subtraction integer arithmetic operations. The test was carried out before and after the learning treatment. The collected data were analyzed using statistical methods to see differences in learning outcomes between using visual aids and those using conventional methods. The results of this study are expected to provide an overview of the effectiveness of using number line teaching aids in improving students' mathematics learning outcomes.This study has the potential to contribute to the development of a more interactive and effective method of learning mathematics, especially in understanding the concept of arithmetic operations on integers. The results of this study can be a consideration for teachers and schools in choosing the right learning strategy to improve students' understanding of mathematics.